2014
DOI: 10.1177/0363546514539914
|View full text |Cite
|
Sign up to set email alerts
|

Lacrosse Injuries Among High School Boys and Girls in the United States

Abstract: Lacrosse injury rates and patterns among high school athletes in the United States differ by type of athletic activity and sex. Future studies should continue to compare differences in injury rates and patterns in high school lacrosse, with particular emphasis placed on high-risk plays in competition and the prevention and management of concussions in both boys and girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
71
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 23 publications
(42 reference statements)
9
71
1
Order By: Relevance
“…Previous research has found that competition injury rates were higher than practice injury rates (Dick et al 2007a; Hinton et al 2005; McCulloch and Bach 2007; Xiang et al 2014). Even with a more inclusive injury definition (including NTL injuries), our study found a similar competition vs. practice injury rate ratio.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous research has found that competition injury rates were higher than practice injury rates (Dick et al 2007a; Hinton et al 2005; McCulloch and Bach 2007; Xiang et al 2014). Even with a more inclusive injury definition (including NTL injuries), our study found a similar competition vs. practice injury rate ratio.…”
Section: Discussionmentioning
confidence: 90%
“…These data include NTL injuries, which had not been previously captured in past injury surveillance efforts (Dick et al 2007a; Xiang et al 2014). These findings provide a wider breadth of the type of injuries sustained by men’s lacrosse athletes and managed by ATs.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 At the high school level, the most frequently reported injuries in boys' and girls' lacrosse were sprains/strains and concussions. 6 At the high school level, both sexes were more likely to sustain an injury during a game than during a practice. 6 In boys' lacrosse, the most common mechanism of injury was contact with another person, including activities such as general play and body checking by another person.…”
mentioning
confidence: 98%
“…5 Studies of girls' lacrosse have shown higher rates of head, face, and eye injuries, most likely because of the lack of any required head/face protection other than a mouth guard at the time. 6 Although similar to a number of sports, such as football and soccer, the potential level of physical contact coupled with rapid deceleration and cutting involved in competitive lacrosse may predispose participants to a variety of injuries. Based on the recent increase in participation, especially among young individuals, 2 and the specific demands of the sports, it is important to understand the most common mechanisms of injury, types of diagnosed injuries, and injured body parts.…”
mentioning
confidence: 99%
“…In sports played by both sexes, girls experience higher concussion rates than boys (Covassin, Moran, & Elbin, 2016;Gessel, Fields, Collins, Dick, & Comstock, 2007;Marar, McIlvain, Fields, & Comstock, 2012), and girls are more likely to report past concussions than boys (Miyashita, Diakogeorgiou, & VanderVegt, 2016). Differences in sports practices and rules may explain some of this differencefor instance, helmets are required for high school lacrosse for males but not females (Xiang, Collins, Liu, McKenzie, & Comstock, 2014). Other possible explanations for increased risk for concussions among females have included biomechanical variations (e.g., neck strength and mass), hormonal differences, social pressure to withhold reporting among males, and differences in concussion severity or symptomology (Covassin & Elbin, 2011;Eckner, Oh, Joshi, Richardson, & Ashton-Miller, 2014;Raukar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%